Cluster 3 CIS Selected Modes - CDPP (CNES, 2022)
This dataset contains CIS status indicators for spacecraft Cluster 3 : Telemetry rate, CIS operational mode, CODIF and HIA operating flags, CIS Solar-wind mode flag - CODIF sensitivity (HS/LS), CODIF RPA and Magnetosheath modes flags